Enhancing the effectiveness of human-robot teaming with a closed-loop system. (February 2018) - Teo, Grace; Reinerman-Jones, Lauren; Matthews, Gerald; Szalma, James; Jentsch, Florian; Hancock, Peter
Abstract: With technological developments in robotics and their increasing deployment, human-robot teams are set to be a mainstay in the future. To develop robots that possess teaming capabilities, such as being able to communicate implicitly, the present study implemented a closed-loop system. This system enabled the robot to provide adaptive aid without the need for explicit commands from the human teammate, through the use of multiple physiological workload measures. Such measures of workload vary in sensitivity and there is large inter-individual variability in physiological responses to imposed taskload. Workload models enacted via closed-loop system should accommodate such individual variability. The present research investigated the effects of the adaptive robot aid vs. imposed aid on performance and workload. Results showed that adaptive robot aid driven by an individualized workload model for physiological response resulted in greater improvements in performance compared to aid that was simply imposed by the system. Highlights: Development of a closed-loop system based on physiological workload measures. Model accommodated inter-individual variability in workload responses. Aid examined in the study was more helpful during high taskload. Aid adapted to the individual's workload response was better than imposed aid. Implications for real-time workload monitoring and adaptive systems.